The Influence Of Esg Performance And Sustainability Reports On The Financial Performance Of Indonesian Companies In 2014 – 2023 - Pangaribuan, Thomas Ariel Hasiando; Rokhim, Rofikoh (UNIVERSITAS PAKUAN, 2024)
This research uses data from 31 public companies listed on the Indonesia Stock Exchange (IDX) over a span of 10 years (2014 – 2023). This study employs the panel data regression method with a Fixed Effect on Model A – ESG and a Random Effect on Model B – Sustainability Report. It was found that the Environment pillar has a negative and significant effect on ROA, however, the Social and Governance pillars have a positive and insignificant effect on ROA. The presence of a Sustainability Report has a negative and insignificant effect on the ROA of companies in Indonesia